Out-of-hospital cardiac arrest in the Pilsen Region in 2018 - Sin, Robin; Vodehnalova, Ivana; Ralbovska, Denisa Charlotte; Struncova, Denisa; Cechurova, Lenka (Biomedical papers, 2021)
Aims. To acquire epidemiological data on pre-hospital cardiac arrest incidents occurring in the Pilsen Region of the Czech Republic in 2018, and the results of subsequent cardiopulmonary resuscitation Methods. A prospective observational study of the survival rate of out-of-hospital cardiac arrest (OHCA) in patients undergoing CPR carried out by emergency medical service personnel. The observed time period was from January 1st, 2018 until December 31st, 2018. The data were acquired from patients' records in paper and electronic forms. Results. In the monitored period 707 patients with signs of cardiac arrest were recorded in the Pilsen Region with an incidence rate of 128.9 per 100,000 inhabitants. Emergency medical units performed CPR in 484 cases. The incidence rate of pre-hospital CPR was 88.2 cases per 100,000 inhabitants. Spontaneous blood circulation was temporarily or permanently restored in 276 patients (57.0%), 203 (41.9%) patients were transferred to a hospital, and there were 61 (12.6%) cases of survival with Cerebral Performance Category (CPC) score of 1 or 2. The first monitored rhythm was a shockable in 134 (27.7%) cases. In this sub-group ROSC was achieved in 94 (70.1%) cases and 58 (43.3%) of those were subsequently transferred to a hospital. A good CPC result was achieved in 41 (30.6%) patients of this sub group. Conclusion. The study has provided valuable epidemiological data on OHCA and prehospital CPR in the area of the Pilsen Region in 2018. The collected data, compared to international results, show a higher survival rate with good neurological score in 12.6% of cases.
Keywords: out-of-hospital cardiac arrest; cardiopulmonary resuscitation; cerebral performance category; emergency medical service